Tributyltin (TBT) toxicity: Effects on enteric neuronal plasticity and intestinal barrier of rats' duodenum - Oliveira, I. C.C.S. [UNESP]; Marinsek, G. P. [UNESP]; Correia, L. V.B.; da Silva, R. C.B.; Castro, I. B.; Mari, R. B. [UNESP] (Elsevier, 2024)
Tributyltin (TBT) is a biocide used in the formulation of antifouling paints and it is highly harmful. Despite the ban, the compound persists in the environment, contaminating marine foodstuffs and household products. Therefore, considering the route of exposure to the contaminant, the gastrointestinal tract (GIT) acts as an important barrier against harmful substances and is a potential biomarker for understanding the consequences of these agents. This work aimed to evaluate histological and neuronal alterations in the duodenum of male Wistar rats that received 20 ng/g TBT and 600 ng/g via gavage for 30 consecutive days. After the experimental period, the animals were euthanized, and the duodenum was intended for neuronal histochemistry (total and metabolically active populations) and histological routine (morphometry and histopathology). The results showed more severe changes in neuronal density and intestinal morphometry in rats exposed to 20 ng/g, such as total neuronal density decrease and reduction of intestinal layers. In rats exposed to 600 ng/g of TBT, it was possible to observe only an increase in intraepithelial lymphocytes. We conclude that TBT can be more harmful to intestinal homeostasis when consumed in lower concentrations.
Keywords: Antifouling; Enteric nervous system; Histopathology; Morphology